Financial Distress: Lifecycle and Corporate Restructuring - Koh, S.; Durand, Robert; Dai, L.; Chang, M. (Elsevier BV * North-Holland, 2015)
A firm's lifecycle consists of birth, growth, maturity and decline. We examine the strategies that firms choose when facing financial distress and present evidence that these choices are influenced by the corporate lifecycle. This influence is most pronounced in the choice of financial restructuring strategies such as reducing dividends or changing capital structure. We also examine if the way firms face financial distress affects the likelihood of recovery. We find that reducing investment and dividends are associated with recovery for all firms, but there is little influence of lifecycle.